STUDY OF NON-ASSIMILATING STUDENTS IN PSYCHOLOGICAL SOURCES IN FOREIGN LITERATURE - Zaynobbiddinov Jaloldin (Galaxy International Interdisciplinary Research Journal, 2022)
The problem of low absorption of students in foreign psychology has been thoroughly studied by the following scientists. Vygotsky, S.L. Rubinstein, A.N. Leontiev, B.F. Lomov, B.D. Parygin, R.H. Shakurov. These scientists believed that the main reason for the inability to learn is the influence of various psychological barriers, special attention is paid to different types of psychological barriers: semantic (L.I. Bojovich, M.S. Neimark), emotional, tactical (L.B. Filonov), communication obstacles (V.A. Kan-Kalik, N.N. Obozov, B.D. Parigin), obstacles in pedagogical activity (A.K. Markova). , N.A.Podymov), innovation barriers (A.M.Khon, A.I.Prigojin, L.S.Podimova). At the same time, the psychological barrier is considered from different positions, depending on the understanding of its nature, essence and methods of analysis. The science of psychology has collected certain theoretical and empirical materials that reveal the specific features of the psychology of students’ learning. The following scientists determined the psychological characteristics of students as subjects of education B.G. Ananiev, G.S. Sukhobskaya, G.S. Vershlovsky, S.L. Rubinstein, A. V. Brushlinsky, these scientists proved that there is a possibility of a person’s successful educational activity in their scientific research work. K.A. Abulkhanova-Slavskaya, L.I. Antsyferova, L.S. Vygotsky, A.A. Bodalev, A. Maslow, K. Rogers, V. Frankl. Z.I. Kalmykova, N.A. Menchinskaya, Y.K. Babansky, L.S. Slavina and others tried to determine the directions of knowledge formation for them by regularly observing the students with low assimilation. For students with low mastery, the developers identify problems related to the formation of strong skills and knowledge, interest, independent thinking, strong-willed qualities, etc.